Braxon®-assisted prepectoral breast reconstruction: A decade later - Bassetto, Franco; Pandis, Laura; Facchin, Federico; Azzena, Gian Paolo; Vindigni, Vincenzo (Frontiers in Surgery, 2022)
We are sitting on the cusp of the bioengineered breast era, in which implant-based breast reconstruction is seeing a growing trend and biotechnology research progressively empowers clinical practice. As never before, the choice of biomaterials has acquired great importance for achieving reconstructive outcomes, and the increase in the use of acellular dermal matrices (ADMs) in the field of senology tells us a story of profound upheaval and progress. With the advent of prepectoral breast reconstruction (PPBR), plenty of devices have been proposed to wrap the silicone prosthesis, either completely or partially. However, this has caused a great deal of confusion and dissent with regard to the adoption of feasible reconstructive strategies as well as the original scientific rationale underlying the prepectoral approach. Braxon® is the very first device that made prepectoral implant positioning possible, wrapping around the prosthesis and exerting the proven ADM regenerative potential at the implant–tissue interface, taking advantage of the body's physiological healing mechanisms. To date, the Braxon® method is among the most studied and practiced worldwide, and more than 50 publications confirm the superior performance of the device in the most varied clinical scenarios. However, a comprehensive record of the working of this pioneering device is still missing. Therefore, our aim with this review is to lay a structured knowledge of surgery with BRAXON® and to provide a decision-making tool in the field of PPBR through a complete understanding on the very first device for prepectoral, one decade after its introduction.